Novel climates reverse carbon uptake of atmospherically dependent epiphytes: Climatic constraints on the iconic boreal forest lichen Evernia mesomorpha. Issue 2 (26th February 2018) - Smith, Robert J.; Nelson, Peter R.; Jovan, Sarah; Hanson, Paul J.; McCune, Bruce
Abstract : Premise of the Study: Changing climates are expected to affect the abundance and distribution of global vegetation, especially plants and lichens with an epiphytic lifestyle and direct exposure to atmospheric variation. The study of epiphytes could improve understanding of biological responses to climatic changes, but only if the conditions that elicit physiological performance changes are clearly defined. Methods: We evaluated individual growth performance of the epiphytic lichen Evernia mesomorpha, an iconic boreal forest indicator species, in the first year of a decade‐long experiment featuring whole‐ecosystem warming and drying. Field experimental enclosures were located near the southern edge of the species' range. Key Results: Mean annual biomass growth of Evernia significantly declined 6 percentage points for every +1°C of experimental warming after accounting for interactions with atmospheric drying. Mean annual biomass growth was 14% in ambient treatments, 2% in unheated control treatments, and −9% to −19% (decreases) in energy‐added treatments ranging from +2.25 to +9.00°C above ambient temperatures. Warming‐induced biomass losses among persistent individuals were suggestive evidence of an extinction debt that could precede further local mortality events. Conclusions: Changing patterns of warming and drying would decrease or reverse Evernia growth at its southern range margins, with potential consequences for the maintenance of local and regional populations. Negative carbon balances among persisting individuals could physiologically commit these epiphytes to local extinction. Our findings illuminate the processes underlying local extinctions of epiphytes and suggest broader consequences for range shrinkage if dispersal and recruitment rates cannot keep pace.